Strategi Kampanye Politik Politisi Muda PKS Dalam Merebut Dukungan Konstituen - Enjang Pera Irawan (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
After the reforms that were launched in 1998, now politics in Indonesia is increasingly dynamic. Indonesian politics is now not only dominated by senior politicians, but also young politicians have emerged. These young politicians are also very aggressive in campaigning to win people's votes. What they highlight is that young politicians are relatively clean and have not been exposed to past political sins. This study aims to analyze the Political Campaign Strategy of Young Politicians of Prosperous Justice Party (PKS) in Seizing Constituent Support in 2019 political contestant. The method used in this research was descriptive qualitative method. The results show that the political campaign strategy of young politicians of Prosperous Justice Party (PKS) in seizing constituent support included seven stages. First, analyzing the political map, which was analyzing the social conditions of the region that would be used as a campaign site. Second, determining the target of votes. Third, forming a campaign team by forming a successful team to help the campaign process. Fourth, formulating a campaign strategy. Fifth, analysis of social connections (networks). Sixth, organizing campaigns by setting campaign schedules. Seventh, escorting the vote result by selecting and determining witnesses and volunteers in the electoral process in escorting the election process and vote result.